A Case Report: Dengue Fever with Right Quadriceps Hematoma - Jha, Birendra; Bhattarai, Ujjwol; Pandey, Bikash; Thapa, Ram; Devkota, Neha; Adhikari, Shital (Nepalese Respiratory Journal, 2025)
Muscle hematomas are rare complications in dengue fever. We report a case of a 40-year-old male patient admitted with dengue fever, complicated by a spontaneous right quadriceps hematoma. The patient with NS1-positive presented with a low platelet count, 20,000/μL. During his hospital stay, the patient developed swelling and pain in the right thigh, and a right quadriceps muscle hematoma was confirmed by ultrasonography (USG). His hemoglobin level was 7.6 g/dL and his hematocrit was 22.1%. He received one pint of packed red blood cells (PRBC) along with supportive care. Monitoring of laboratory parameters, including the size of the hematoma was done until it resolved spontaneously. Despite its rarity, we must recognize and manage this dengue fever complication appropriately. Such complications have not been well documented in the literature.